Pressure Membrane FBG Sensor Realized by 3D Technology - Fajkus, Marcel; Nedoma, Jan; Martinek, Radek; Fridrich, Michael; Bednar, Emil; Zabka, Stanislav; Zmij, Petr (Sensors (Basel, Switzerland), 2021)
The publication describes the design, production, and practical verification of an alternative pressure sensor suitable for measuring the pressure of gas, based on a combination of fiber-optic technology and 3D printing methods. The created sensor uses FBG (Fiber Bragg Grating) suitably implemented on a movable membrane. The sensor is equipped with a reference FBG to compensate for the effect of ambient temperature on the pressure measurement. The sensor is characterized by its immunity to EM interference, electrical passivity at the measuring point, small size, and resistance to moisture and corrosion. The FBG pressure sensor has a pressure sensitivity of 9.086 pm/mbar in the range from 0 to 9 mbar with a correlation coefficient of 0.9982. The pressure measurement in the specified range shows an average measurement error of 0.049 mbar and a reproducibility parameter of 0.0269 ± 0.0135 mbar.
Keywords: technologie optických vláken; pressure; Fiber Optic Technology; Reproducibility of Results; technologie; 3D technology; reprodukovatelnost výsledků; measurement; optická vlákna; fiber Bragg grating; Optical Fibers; Technology